Interplay between triglyceride-glucose index and cardiovascular events in hypertensive patients with controlled blood pressure (SBP<140 mmHg): insights from the SPRINT trial - Chen, Xiaoling; Wang, Lili; Jiang, Yingying; Tang, Wenyi; Xiao, Jun; Deng, Wuquan; Ren, Xiangpeng; Li, Chuanwei (Frontiers in Endocrinology, 2025)
IntroductionHypertension significantly contributes to cardiovascular events and global all-cause mortality. The triglyceride-glucose (TyG) index, amarker of insulin resistance (IR), is an established risk factor for cardiovascular disease (CVD) events. This study examined the relationship between the TyG index and cardiovascular events in patients with controlled hypertension (SBP <140 mmHg).MethodsWe performed a post-hoc analysis of data from the Systolic Blood Pressure Intervention Trial (SPRINT), involving 9,323 participants with controlled hypertension. The triglyceride-glucose (TyG) index served as a surrogate marker for IR. Cox restricted cubic regression analysis and multivariate Cox regression models were employed to investigate the association between the TyG index and CVD outcomes, adjusting for established cardiovascular risk factors. The impact of intensive versus standard BP control on CVD risk associated with high IR levels were also analyzed.ResultsOver a median follow-up of 3.33 years, 725 CVD events were recorded. The TyG index was independently linked to a heightened risk of CVD events,with the highest quartile (Q4:8.93≤TyG<12.47) exhibiting a significantly greater risk (HR = 1.57, 95% CI: 1.18–2.08) compared to the lowest quartile (Q1: 6.74 ≤ TyG < 8.21). The significantly trend was seen only in the standard treatment group (p for trend = 0.001).DiscussionThe TyG index is a robust predictor of CVD events in patients with controlled hypertension, and a stronger association between the TyG index and CVD risk was seen in the standard treatment group, but not in the intensive 1treatment group.Clinical trial registrationhttp://www.clinicaltrials.gov, identifier NCT01206062.